The Effect of a Computerized Growth-Mindset Intervention on Teaching Students’ Mindset and Cognitive Stress Appraisal - Montagna, Melissa Joy; Marksteiner, Tamara; Dickhäuser, Oliver (Frontiers in Education, 2021)
The present study assessed the impact of a one-time computerized mindset intervention on teaching-students’ cognitive stress-appraisal before an upcoming exam. Previous research highlights the long-term effectiveness of growth-mindset interventions (Aronson, Fried, & Good, 2002; Paunesku et al., 2015). Based on theoretical assumptions derived from the transactional stress theory (Lazarus, 1966) as well as recent empirical evidence on intelligence-mindset and stress (Lee, Jamieson, Miu, Josephs, & Yeager, 2019), we proposed that changing students’ mindset would also impact their cognitive stress-appraisal. In order to test this hypothesis a sample of teaching-students received a one-time computerized growth-mindset intervention aiming to foster viewing abilities as incremental. We found a significant as well as relatively lasting impact on participants’ mindset but no significant effect on participants’ stress-appraisal. Nevertheless, an exploratory mediation analysis revealed that the intervention’s effect on participants’ appraisal of their coping ability (as part of the cognitive stress-appraisal) was fully mediated by participants’ mindset. The results highlight the effectiveness of the utilized intervention and provide first practical insights into how a person’s mindset and their stress-appraisal relate.